Application of sonication and freezing as initial treatments before microwave-vacuum drying of cranberries - Staniszewska, Izabela; Staszyński, Szymon; Zielińska, Magdalena (Technical Sciences, 2019)
The aim of study was to determine the influence of sonication and freezing on the kinetic of the microwave-vacuum drying, energy consumption and physical properties of whole cranberries as well as evaluate the applicability of sonication instead of freezing in order to change their physical properties and the drying kinetic of whole cranberries. Microwave-vacuum drying of whole cranberries with/without initial treatments took from 12 ± 1 to 14.5 ± 0.5 minutes. All of treatments did not significantly shorten the drying time of cranberries. However, they increased SMER values even by 31%. Despite of cryogenic freezing, all of treatments significantly increased the values of Dew. Sonication combined with drying allowed to obtain dried berries characterized by the lowest cohesiveness (0.19±0.02), springiness (0.62±0.02) and chewiness (3.4±0.8 N), while cryogenic freezing combined with drying allowed to obtain dried fruits characterized by highest springiness (0.75±0.03) and low chewiness (3.3±0.5 N). The highest lightness (32.2±0.7), redness (32.6±0.8), and yellowness (11.1±0.7) were found for fruits subjected to initial convective freezing before drying. The efficiency of sonication in color change was comparable to cryogenic freezing and much lower than convective freezing. All of initial treatments increased such thermal properties of dried cranberries as thermal conductivity and thermal diffusivity.